2012
DOI: 10.1007/s13594-012-0062-9
|View full text |Cite
|
Sign up to set email alerts
|

High-pressure treatment applied throughout ripening of a goat cheese caused minimal changes on free fatty acids content and oxidation in mature cheese

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…Our results agree with the reported in blue-veined cheese, which showed no significant differences in MCFA concentrations between cheeses treated at 600 MPa for 5 min at day 63 of ripening and control cheeses after 270 days of storage (Calzada et al 2013). Similar results have also been found in raw goat's milk cheese which showed non-significant differences in MCFA concentrations on day 60 between pressurised and control cheeses (Delgado et al 2012).…”
Section: Free Fatty Acids In Hp-treated Torta Del Casar Cheesesupporting
confidence: 92%
“…Our results agree with the reported in blue-veined cheese, which showed no significant differences in MCFA concentrations between cheeses treated at 600 MPa for 5 min at day 63 of ripening and control cheeses after 270 days of storage (Calzada et al 2013). Similar results have also been found in raw goat's milk cheese which showed non-significant differences in MCFA concentrations on day 60 between pressurised and control cheeses (Delgado et al 2012).…”
Section: Free Fatty Acids In Hp-treated Torta Del Casar Cheesesupporting
confidence: 92%
“…The content of short chain FFAs only decreased in cheeses treated at 600 MPa at the first ripening day. Medium and long FFA content did not vary with any of the HHP treatments [ 45 , 65 ]. Inácio et al [ 56 ] reported a significant reduction in the microbial count of Enterobacteriaceae , Listeria innocua , molds and yeasts in raw milk ewe’s cheeses treated with high pressure.…”
Section: High Hydrostatic Pressure (Hhp) Processingmentioning
confidence: 99%
“…HHP treatments can influence cheese proteolysis by modifying the conformational structure of the proteins, activation or inactivation of proteinases, and inhibition or acceleration of the microbial growth and metabolism [ 66 ]. Studies showed that pressure intensity and the time of application are crucial to maintain the cheese’s texture and flavor characteristics [ 54 , 60 , 65 ]. Changes during ripening can be due to an increase in primary or secondary proteolysis when using 200–400 MPa HHP treatments.…”
Section: High Hydrostatic Pressure (Hhp) Processingmentioning
confidence: 99%